2009
DOI: 10.1007/s11605-009-0818-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of Non-operative Therapy for Delayed Hemorrhage after Pancreaticoduodenectomy

Abstract: Conservative management, combining endovascular procedures and aggressive resuscitation, is appropriate for most cases of delayed hemorrhage after pancreaticoduodenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 32 publications
3
34
0
1
Order By: Relevance
“…In our experience, arteriography plays the primary role in the initial investigation of active gastrointestinal bleeding after pancreatoduodenectomy and should be the first step of investigative procedure in such situations, even in hemodynamically unstable patients. It was reported that the gastroduodenal artery stump is one of the main sources of pancreaticojejunal anastomotic hemorrhage after pancreatoduodenectomy [3] , as confirmed in this study. Selective angiography of the celiac trunk and common hepatic artery allows in the majority of cases to detect extravasation of contrast medium.…”
Section: To the Editorsupporting
confidence: 87%
See 1 more Smart Citation
“…In our experience, arteriography plays the primary role in the initial investigation of active gastrointestinal bleeding after pancreatoduodenectomy and should be the first step of investigative procedure in such situations, even in hemodynamically unstable patients. It was reported that the gastroduodenal artery stump is one of the main sources of pancreaticojejunal anastomotic hemorrhage after pancreatoduodenectomy [3] , as confirmed in this study. Selective angiography of the celiac trunk and common hepatic artery allows in the majority of cases to detect extravasation of contrast medium.…”
Section: To the Editorsupporting
confidence: 87%
“…Transcatheter embolization is now accepted as the salvage treatment of choice for acute bleeding from the upper gastrointestinal tract. Many published studies have confirmed the feasibility of this approach and the high technical and clinical success rates, ranging from 91% to 100% and from 63% to 100%, respectively, in all case-series including more than 10 patients over the last decade [2,3] . First, we are surprised in this study that 6 (35.3%) of the 17 patients had no angiography prior to additional open surgical hemostasis.…”
Section: To the Editormentioning
confidence: 99%
“…Delayed haemorrhage invariably occurs in association with a pancreatic anastomotic leak with an associated pancreatic fistula or a biliary leak [17] and rarely, stress-induced gastric erosion. Intra-abdominal infection and sepsis result in delayed haemorrhage by erosion of ligated blood vessels in the region around the pancreatic anastomosis viz., gastroduodenal artery, pancreatic branches of the proximal splenic artery, superior mesenteric vein, portal vein and superior mesenteric artery and its branches [18,19].…”
Section: Delayed Haemorrhagementioning
confidence: 99%
“…Delayed haemorrhage is invariably associated with a pancreatic anastomotic leakage [13][14][15][16][17] and therefore prevention of delayed haemorrhage is almost always dependent on a well done and secure pancreatic anastomosis. The various aspects on pancreatic anastomosis would be discussed in the section dealing with the preventive aspects of pancreatic anastomotic leak and fistula.…”
Section: Prevention Of Pphmentioning
confidence: 99%
“…Post-PD arterial bleeding usually happens late (>5 days postoperatively). Because of the lack of a generally accepted definition, the reported prevalence of this fatal complication varies widely (1.5–20.2%) [16,17,18,19,20,21,22]. Delayed post-pancreaticoduodenectomy arterial bleeding (DPPAB) is usually massive, with impairment of the peripheral circulation.…”
Section: Introductionmentioning
confidence: 99%